Trignometric Expressions
Trignometric Expressions
Trignometric Expressions
com
TRIGONOMETRIC EXPANSIONS
sin 4θ
1. Show that = 8cos3 θ − 4 cos θ
sin θ
Solution: -
We know that 1 cos n −1 θ sin θ − nc3 cos n −3 θ sin 3 θ + nc5 cos n −5 θ sin 5 θ ..........
sin 4θ = 3c1 cos 3 θ sin θ − 4c3 cos θ sin 3 θ
{
= 4c1 sin θ 4 cos3 θ − 4 cos θ sin 2 θ }
sin 4θ
sin nθ
{
= 4 cos3 θ − cos θ (1 − cos 2 θ ) }
sin 4θ
= 8cos3 θ − 4 cos θ
sin nθ
{ ( ( )
) {
= cos7 θ − 21 cos5 θ 1 − cos 2 θ + 35cos3 θ 1 − cos 2 θ − 7 cos θ 1 − cos 2 θ
2
}}
3
+ 21sin 5 θ − 21sin 7 θ
= 7 sin θ − 56sin 3 θ + 112 sin 5 θ − 64 sin 7 θ
www.sakshieducation.com
www.sakshieducation.com
x x
1 1 1 1 1 1
x 6 + 6c1 x 5 + 6c2 x 4 2 + 6c3 x 3 3 + 6c4 x 2 4 + 6c5 x + 5 + 6c6 6 = 26 cos 6 θ
x x x x x x
6 1 4 1 2 1
x + 6 + 6 x + 4 + 15 x + 2 + 20 = 64 cos θ
6
x x x
2cos 6θ + 6 ( 2cos 4θ ) + 15 ( 2cos 2θ ) + 2θ = 64cos6 θ
cos 6θ + 6cos 4θ + 15cos 2θ + 10 = 32 cos6 θ
www.sakshieducation.com
www.sakshieducation.com
x x
15 6 1
x 6 − 6 x 4 + 15 x 2 − 20 + 2 − 4 + 6 = 26 i 6 sin 6 θ
x x x
6 1 4 1 2 1
x + 6 − 6 x + 4 + 15 x + 2 − 20 = − 2 {2 sin θ }
5 6
x x x
2 cos 6θ − 6 ( 2 cos 4θ ) + 15 ( 2 cos 2θ ) − 20 = − 2 {32 sin 6 θ }
10 − 15 cos 2θ + 6 cos 4θ − cos 6θ = 32 sin 6 θ
x x
5c 5c 5c
x5 − 5c1 x3 + 5c2 x − 3 + 34 − 55 = 25 i 5 sin 5 θ
x x x
5 1 3 1 1
x − 5 − 5 x − 3 + 10 x − = 32 i sin θ
5
x x x
2i sin 5θ − 5 ( 2i sin 3θ ) + 10 ( 2i sin θ ) = 32i sin 5 θ
{
2i {sin 5θ − 5sin 3θ + 10sin θ } = 2i 16sin5 θ }
∴16sin 5 θ = sin 5θ − 5sin 3θ + 10 sin θ
x x
www.sakshieducation.com
www.sakshieducation.com
2 3
1 1 1
x + x − x − = 2 i sin θ cos θ
7 5 5 2
x x x
2
2 1 3 3x 3 3
x − 2 x − + − 3 = 27 i sin 5 θ cos 2 θ
x x x x
4 1 3 3 1
x + 4 − 2 x − 3 x + − 3 = 2 i sin θ cos θ
7 5 2
x x x
1 1 3 3 1 6 2
x7 − 3x5 + 3x3 − + − 3 + 5 − 7 − 2 x3 + 6 x − + 3
2 x x x x x x
2 i sin θ cos θ
7 5 2
7 1 5 1 3 1 1
x − 7 − 3 x − 5 + x − 3 + 6 x − = 2 i sin cos θ
7 5 2
x x x x
{
2i sin 7θ − 3 ( 2i sin 5θ ) + 2i sin 3θ + 6 ( 2i sin θ ) = 2i 64 sin 5 θ cos 2 θ }
{
2i {sin 7θ − 3sin 5θ + sin 3θ + 6sin θ } = 2i 64sin 5 θ cos 2 θ }
5. Show that 32cos2 θ sin 4 θ = cos 6θ − 2cos 4θ − cos 2θ + 2
Solution : -
1
Let x = cos θ + i sin θ = cos θ − i sin θ
x
1 1
x + = 2 cos θ x − = 2i sin θ
x x
1 1
x n + n = 2 cos nθ x n − n = 2i sin nθ
x x
2 4
1 1
x + x + = ( 2 cos θ ) ( 2i sin θ )
2 4
x x
2 2
1 1 1
x + x − x − = 4 cos θ 16i sin θ
2 4 4
x x x
2 2
2 1 1
x − 2 x − = 64 cos θ sin θ
2 4
x x
4 1 2 1
x + 4 − 2 x + 2 − 2 = 64 cos θ sin θ
2 4
x x
1 1 2 2
x 6 + x 2 − 2 x 4 + 2 + 6 − 4 − 2 x 2 − 2 + 4 = 64 cos 2 θ sin 4 θ
x x x x
6 1 4 1 2 1
x + 6 − 2 x + 4 − x + 2 + 4 = 64 cos θ sin θ
2 4
x x x
2 cos 6θ − 2 ( 2 cos 4θ ) − 2 cos 2θ + 4 = 64 cos 2 θ sin 4 θ
cos 6θ − 2 cos 4θ − cos 2θ + 2 = 32 cos 2 θ sin 4 θ
www.sakshieducation.com
www.sakshieducation.com
KEY CONCEPTS
www.sakshieducation.com